Geografia do voto no Tocantins: influências e disputas territoriais nos processos eleitorais entre 2002 e 2014 - Naves, Witer Fonseca (Universidade Federal do Tocantins, 2020)
This dissertation discusses Electoral Geography, the behavior and practices of candidates and parliamentarians in electoral influences and disputes, from 2002 to 2014, observing the formation of their constituencies and the search for practices that led elected representatives to win their votes. As we study these disputes, we conclude that distributivism is a significant concept in the behavior of deputies in the constitution of their constituencies, thus generating a taxonomy of spatial patterns for obtaining a seat in the Legislative Assembly. The determination of electoral seniority is a trait to represent patrimonialist and colonelist practices still alive in the Brazilian and Tocantins political environment. The research is pertinent, for the reason of bringing a scientific contribution to the study of the electoral processes in the newest state of the Brazilian federation. Even knowing our limitations of conclusions, given by the difficulty of gathering information, throughout the work and, which eventually lead us to another way in research, from the relationship between parliamentary behavior and its territorial disputes and influences. In this perspective, therefore, we advance in the path of science. However, we seek a scientific approach to understanding the power relations within Brazilian democracy